2018
DOI: 10.1108/ijrdm-01-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Online customer experience (OCE) in clothing e-retail

Abstract: Purpose The purpose of this paper is to explore the dimensions of online customer experience (OCE) and their impact on satisfaction and loyalty in the clothing e-retail context. Furthermore, it explores the influence of gender on the OCE-satisfaction-loyalty chain. Design/methodology/approach OCE dimensions were drawn from the literature and then adapted and validated using two samples (217 – exploratory factor analysis, 651 – confirmatory factor analysis) of experienced online clothing shoppers in India. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 76 publications
4
44
2
7
Order By: Relevance
“…However, various researchers [22,34] use those factors to operationalize CX. While the majority of researchers, for example Pandey and Chawla [27], used enjoyment to measure CX, other researchers used this factor as an antecedent [17]. It follows that there is little agreement on how to measure CX in retail and what drives it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, various researchers [22,34] use those factors to operationalize CX. While the majority of researchers, for example Pandey and Chawla [27], used enjoyment to measure CX, other researchers used this factor as an antecedent [17]. It follows that there is little agreement on how to measure CX in retail and what drives it.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, researchers highlight a hedonic [16] and affective [17][18][19][20] experience, an emotional experience [21], positive in-shop emotions [22,23], feelings [24], and dominance, pleasure, and arousal [25,26]. Enjoyment is the most researched emotion [25,[27][28][29], and Foroudi et al [16] add the viewpoint of customers' recognition (e.g. a feeling of importance).…”
Section: Is a Multidimensional Constructmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous study has shown a positive relationship between perceptions of pleasure and online shopping attitudes, as well as customer emotions and satisfaction with the company (Verhagen and van Dolen, 2011;Lee et al, 2016). Furthermore, the level of customer satisfaction will lead to the level of customer loyalty to the company (Pandey and Chawla, 2018). Based on this relationship, the research hypothesis is proposed as follows: H1: E-Enjoyment has a positive impact on website satisfaction and loyalty…”
Section: E-enjoymentmentioning
confidence: 95%
“…However, SITEQUAL does not provide a comprehensive evaluation of the website (Parasuraman et al, 2005 Loiacono (2002) do not yet represent an essential antecedent in shaping customer satisfaction and loyalty. Pandey and Chawla (2018) develop the functional and psychological dimensions of online consumer experience (OCE) towards customer satisfaction and loyalty. The functional and psychological psychology model developed from the Klaus (2013) model, where the functional dimensions of OCE are technical attributes on websites such as usability, communication, social presence, product presence, and interactivity.…”
Section: Literatur Reviewmentioning
confidence: 99%